Inquiry Method: An Effective Strategy to Improve Science Understanding in Science Learning - Nurfaidah, Sitti (Scientica Education Journal, 2025)
This study aims to comprehensively describe the effectiveness of the inquiry method in enhancing students' scientific understanding within the context of Natural Sciences (IPA) learning at the elementary school level. Employing a qualitative research design with a case study approach, the study focused on capturing in-depth insights into the implementation of inquiry-based learning in a real classroom setting. Data collection was carried out through systematic observation, in-depth interviews with teachers and students, and documentation of teaching and learning activities. The findings reveal that the implementation of the inquiry method significantly contributed to increasing students’ active engagement during science lessons. It also fostered a deeper and more meaningful understanding of scientific concepts by encouraging students to explore, question, and construct knowledge through hands-on experiences and guided discovery. Moreover, the inquiry approach effectively developed essential science process skills, such as making detailed observations, classifying information, formulating hypotheses, and drawing evidence-based conclusions. Students demonstrated high levels of enthusiasm, curiosity, and motivation throughout the inquiry-based activities, which further supported their cognitive and affective engagement in learning. While some challenges were encountered—such as the need for adequate teacher preparation, time constraints, and the varying levels of student readiness—the inquiry method nonetheless emerged as a powerful pedagogical strategy. It provided a contextualized, student-centered learning environment that not only aligned with the nature of science but also improved the overall quality and relevance of science instruction. Therefore, this study affirms that the inquiry method holds strong potential as an effective approach to promoting scientific literacy and inquiry-mindedness among young learners in elementary education.